If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x(x-5)=12
We move all terms to the left:
6x(x-5)-(12)=0
We multiply parentheses
6x^2-30x-12=0
a = 6; b = -30; c = -12;
Δ = b2-4ac
Δ = -302-4·6·(-12)
Δ = 1188
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}
The end solution:
\sqrt{\Delta}=\sqrt{1188}=\sqrt{36*33}=\sqrt{36}*\sqrt{33}=6\sqrt{33}x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-30)-6\sqrt{33}}{2*6}=\frac{30-6\sqrt{33}}{12}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-30)+6\sqrt{33}}{2*6}=\frac{30+6\sqrt{33}}{12}
| 2x-5=8x-15 | | 5x+3=2-4x | | (72t)−2=4+7t | | 72t)−2=4+7t | | 2x-100=x+2 | | 1/4+1/2+z=-3/4 | | 11=m–4 | | 2(39x-11)=2(17x+6) | | 39x-11=17+6 | | 39x-11=2(17x+6) | | -3/8-7x=-149/24 | | 2(39x-11)=17x+6 | | 9x+1=-1x+19 | | 14^-9x=3^x-5 | | 5x+5=2x+3+x | | -18x+14-17x=4x | | -15x+122=-8x+66 | | -8x-20=-5x-11 | | 2x-21=x-14 | | 10x+19=15x+29 | | -24x+99=-16x+51 | | -79=-1-6n | | 9p-9=18 | | 3p-6=-54 | | Y=2.3x+6 | | -12=(f-6) | | x²+8+15=63 | | 20+50x=10+5x | | 2n+1=5n= | | 12x+20=19x+18 | | -1.14x+0.26=-10 | | -9/5x-2=-20 |